2020
DOI: 10.1155/2020/2034625
|View full text |Cite
|
Sign up to set email alerts
|

Tai Chi and Qigong Practices for Chronic Heart Failure: A Systematic Review and Meta‐Analysis of Randomized Controlled Trials

Abstract: Background. Several randomized controlled trials (RCTs) have assessed the role of Tai Chi and Qigong Practices (TQPs) in managing chronic heart failure (CHF). They have included broad variations in comparators, sample sizes, and results. This study evaluates existing RCTs for evidence of TQPs rehabilitation effects for CHF. Methods. Both English and Chinese databases were searched from their inception to October 23, 2019. RCTs were included if they compared the addition of TQPs into routine managements (RMs) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
2
11
1
Order By: Relevance
“…The results of 6WMD from this study suggested that TCE could improve the exercise tolerance of HF patients. Our findings are consistent with other systematic reviews and meta-analyses of TCE for HF patients [ 52 , 57 , 58 ]. However, a meta-analysis has reported that Tai Chi did not significantly improve 6MWD in patients with CHF [ 59 ].…”
Section: Discussionsupporting
confidence: 93%
“…The results of 6WMD from this study suggested that TCE could improve the exercise tolerance of HF patients. Our findings are consistent with other systematic reviews and meta-analyses of TCE for HF patients [ 52 , 57 , 58 ]. However, a meta-analysis has reported that Tai Chi did not significantly improve 6MWD in patients with CHF [ 59 ].…”
Section: Discussionsupporting
confidence: 93%
“…e study protocol has been published in PROSPERO (CRD42018081982). We followed the methods of Chen et al (2020) [36].…”
Section: Methodsmentioning
confidence: 99%
“…An earlier systematic review [14] confirmed that Taiji was an effective cardiac rehabilitation practice for patients with HF. Chen et al [15] reported that Taiji and Qigong practices were promising rehabilitation therapies; however, some of their conclusions were based on a large heterogeneity, which was not confirmative. erefore, the effects of TCE on heart failure remain unclear.…”
Section: Introductionmentioning
confidence: 96%